Ustavnosodna presoja na področju individualnih delovnih razmerij - Korpič-Horvat, Etelka (Delavci in delodajalci, 2011)
An employer may collect process and use solely the data related to the facts concerning the identification of violations of the employment relationship of an absence from work due to illness and injury. The ways of collecting information are to be limited regarding the place, time, methods, etc., in order to prevent over-interference into constitutionally protected right to privacy and thus protect human rights of the respective worker of public official.
Keywords: izredna odpoved; javna uprava; javni uslužbenci; odsotnost z dela; osebni podatki; varstvo podakov; zaposleni; zasebnost; zloraba; zloraba bolniške odsotnosti